Transforming the structure of unmarried women’s social perceptions of single motherhood through digital technologies - A. I. Eremeeva; G. V. Dovzhik (Цифровая социология)
The transformation of the structure of social ideas about marriage and family relations in general and the structure of the modern family has been considered through digital technologies. The problem of the growing number of single mothers has been raised. Statistics for 20 years have been provided. The influence of several factors on the growth dynamics has been analysed. The influence of women`s emancipation, availability of remote work and the image of successful bloggers on changing the fields of social representations of modern unmarried women about single motherhood has been examined. One of the main reasons for changing the attitude of women to the image of single mother, namely the appearance of a new image-”solo-mom”, which is actively used in the digital environment, has been considered. Communities and groups in the social networks Vkontakte, Facebook, Instagram and Odnoklassniki, dedicated to supporting single mothers, have been studied. Blogs of single mothers who position themselves as “solo-mothers”, have been reviewed. The results of an empirical study aimed at identifying a factor that affects the change in the system of views and attitudes of unmarried women in the transition zone and the periphery have been presented. The responses of respondents received in 2014 and 2019 by the free Association experiment have been analysed. The respondents answers were divided into three categories: single mother status, status assessment, qualities of the single mother’s personality. The results of a comparative analysis of women’s social perceptions about single motherhood for the period from 2014 to 2019 have been presented. Based on the results obtained, conclusions about the change in perceptions of single mothers over the past 5 years, the emergence of a new image of a single woman with a child – “solo mom”, have been made.